2004
DOI: 10.1080/15287390490483827
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling in Spleens of Deoxynivalenol-Exposed Mice: Immediate Early Genes as Primary Targets

Abstract: Exposure to the trichothecene mycotoxin deoxynivalenol (DON) alters immune functions in vitro and in vivo. To gain further insight into DON's immunotoxic effects, microarrays were used to determine how acute exposure to this mycotoxin modulates gene expression profiles in murine spleen. B6C3F1 mice were treated orally with 25mg/kg body weight DON, and 2h later spleens were collected for macroarray analysis. Following normalization using a local linear regression model, expression of 116 out of 1176 genes was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
35
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 85 publications
10
35
0
1
Order By: Relevance
“…Kinser et al reported that deoxynivalenol upregulated the MCP-1 mRNA in mouse spleen cells 4 , however, they did not document the secretion of MCP-1.…”
Section: Monocyte Chemotactic Protein (Mcp) -1mentioning
confidence: 99%
“…Kinser et al reported that deoxynivalenol upregulated the MCP-1 mRNA in mouse spleen cells 4 , however, they did not document the secretion of MCP-1.…”
Section: Monocyte Chemotactic Protein (Mcp) -1mentioning
confidence: 99%
“…DON was found to induce the cytokines interleukin (IL)-1alpha, IL-1beta, IL-6 and IL-11.DON upregulated expression of the chemokines macrophage inhibitory protein-2 (MIP-2), cytokine-induced chemoattractant protein-1 (CINC-1), monocyte chemoattractant protein (MCP)-1, MCP-3, and cytokine-responsive gene-2 (CRG-2). c-Fos, Fra-, c-Jun, and JunB, components of the activator protein-1 (AP-1) transcription factor complex, were induced by DON as well as another transcription factor, NR4A1 [41,44].…”
Section: Immunology Of Toxicogenomics Gene Therapymentioning
confidence: 99%
“…Many differentially expressed genes are known to play a role in apoptosis, host defense, cell growth and differentiation, and trafficking of specific cells in body fluid systems. In the spleen, these may include the up-regulation of IL-18, lymphotoxin B receptor, and colonystimulating factor receptor, and down-regulation of RANTES and histocompatibility antigens [15,[33][34][35]. In the thymus, gene changes included the down-regulation of nuclear factor of activated T cells, interferon gamma receptor, and T cell transcription factor 7, and the up-regulation of caspase 1 and ApoE.…”
Section: Transcriptomics Study On Medicinal Plant Researchmentioning
confidence: 99%
“…Gene chips or microarrays are already employed in immunotoxicology research to identify biochemical pathways that are altered by specific chemical exposures. For example, trichothecene mycotoxin deoxynivalenol has been shown in mice to modulate splenic early responsive genes, which are functionally related to immunity, inflammation and chemotaxis [15,26], indicating the importance of innate immune systems, including macrophages, granulocytes, neutrophils and various soluble mediators released in the inflammatory response activated by the hexachlorobenzene treatment. For basic research, a number of mechanistic studies have been performed towards gaining a comprehensive understanding of the immunomodulatory properties of potential new drugs or drug leads.…”
Section: Transcriptomics Study On Medicinal Plant Researchmentioning
confidence: 99%
See 1 more Smart Citation